Au-delà du TPL : une analyse de la dysrégulation émotionnelle à travers un cas complexe. - Picard, Natanièle; Guével, Marie-Laurence; Ouellet, Estelle (Sante Mentale au Quebec)
Emotional dysregulation is often quickly attributed to Borderline Personality Disorder (BPD), particularly when repeated emergency department visits are involved. This case study illustrates the importance of a comprehensive, interdisciplinary assessment when the clinical presentation is complex. Johanne (fictional name), a woman in her forties with no prior psychiatric history, became a high user of emergency services following acute psychosocial stressors. For several years, the diagnoses retained were BPD with dependent traits. However, outpatient clinical observations raised doubts about the accuracy of these diagnoses. A thorough reassessment, including a functional occupational therapy evaluation and a neuropsychological assessment, revealed significant cognitive limitations consistent with borderline intellectual functioning. These findings suggested that her crises stemmed less from abandonment fears typical of BPD and more from situations exceeding her cognitive and adaptive capacities. Adjusting the interventions (substantial simplification of Dialectical Behavior Therapy [DBT], emphasis on concrete problem-solving, and clarification of her crisis plan) led to notable improvements, including a marked reduction in emergency visits and a sustained return to employment. This case highlights the risk of prematurely diagnosing BPD when emotional dysregulation is present and underscores the relevance of functional, interdisciplinary assessments to better identify the underlying psychopathology driving emotional dysregulation in complex profiles.